Legal Certainty Concerning Implementation of Working Agreements between Service Providers & Workers Concerning Delay Payments of Work Achievement - Taufan Fajar Riyanto; Ramon Lantemona (Jurnal Akta, 2021)
This study aims to: to determine legal certainty regarding the implementation of work agreements between service providers and employers in the event of a delay in payment of work performance by the service provider. The approach method in this research is normative law, the data source is obtained from the literature and the legal materials used are primary, secondary and tertiary legal materials which are then analyzed by means of qualitative analysis. Based on the results of data analysis, it can be concluded that : With the presence of a work agreement between the service provider and the employer, this agreement basically provides legal certainty regarding the rights and obligations of both parties, one of the points in the payment is the payment for work performance, in this case the service provider is obliged to accept work repayment that has reached 100 % or it has been completed, when the Regional Government of South Konawe Regency, the Office of Food Crops, Horticulture and Plantations does not make payment, the agency has defaulted because in the agreement it was agreed that when the work was completed, a settlement would be carried out. This certainly violates the Principle of Pacta Sunt Servanda (Agreement Applies as Law) as contained in the provisions of Article 1338 paragraph (1) and paragraph (2) of the Civil Code which states that "all agreements legally made are valid as laws for those who make them.